Determinant factors affecting employee’s performance in the state-owned banks sector: mediated by job satisfaction - Herizal, Herizal; Abubakar, Al Asri; Hernita, Nita (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2025)
Purpose – This study analyses job satisfaction, mediating the influence of work-life balance, workplace culture, and compensation on employee performance. Method – This study used a causally associative methodology and a quantitative approach. Employees working in state-owned banking sectors in Aceh were the population in this study. The research sample was 156 employees who were chosen using purposive sampling. The data source uses primary data as a survey by providing questionnaires for employees to fill out. Data analysis techniques use partial least squares-structural equality modeling (PLS-SEM) with statistical tools in SmartPLS software. Findings – Based on the study's findings, work-life balance positively affects employee performance. In contrast, work environment, compensation, and job satisfaction did not affect employees' performance. Job satisfaction can mediate the relationship between compensation and work-life balance on employee performance. However, job satisfaction cannot mediate the relationship between work environment and employee performance. Implications – Theoretically, the results of this study strengthen the understanding that job satisfaction is an important psychological variable that links work environment factors with performance outcomes. These results provide strategic direction for state-owned bank management to focus on creating a work environment that supports work-life balance, a healthy work culture, and an appropriate compensation system to increase satisfaction and ultimately drive optimal employee performance.